Cultivation and Functional Characterization of a Deep-Sea Lentisphaerae Representative Reveals Its Unique Physiology and Ecology - Zhang, Tianhang; Zheng, Rikuan; Liu, Rui; Li, Ronggui; Sun, Chaomin (Frontiers in Marine Science, 2022)
As a member of Planctomycetes–Verrucomicrobia–Chlamydia (PVC) superphylum, the phylum Lentisphaerae is broadly distributed in various environments. Lentisphaerae members have been recognized as being typically difficult to isolate in pure culture—only five strains belonging to this phylum were cultured up to now—and therefore their major physiology and ecology are largely unknown. Here, using a polysaccharide degradation-driven strategy, we successfully cultured a representative of Lentisphaerae bacteria (Candidatus Coldseepensis marina zth2) from the deep-sea cold seep. Based on physiological and phylogenetic analyses, strain zth2 is identified as a type strain of a novel family. Notably, strain zth2 divides by a budding manner and a unique feature seen in ultrathin-section electron microscopic observation is the occurrence of narrow protrusions, namely, both cell wall and cytoplasm on the surface of strain zth2. Through growth assays and transcriptomic analyses, strain zth2 was verified to efficiently utilize polysaccharides, phosphate, and iron for growth. Strikingly, the utilization of polysaccharide, phosphate, and iron is correlative and jointly contributes to carbon, phosphorus, and iron metabolisms and thereby facilitating the production of energy. By mimicking the ocean environment and using operational taxonomic units (OTUs) analysis, we demonstrated that strain zth2 significantly enrich the microbial diversity by metabolizing polysaccharides or other substances. Overall, we propose that Lentisphaerae members are potential contributors to the cycling of nutrient, carbon, phosphorus, and other elements in the deep biosphere.